Decent Work and Representations of Work among Unskilled and Low-Skilled Emerging Adults in France (Revista de Psicología, 2023)
The current labor market context is characterized by a diversification of forms of employment, a transformation of work organizations and a singularization of career paths. This article aims to analyze and describe how young adults conceive their professional future and how they define a decent job. Data were obtained through semistructured interviews with ten young adults. The corpus of interviews was subjected to content analysis. The results show that work is a necessity for young people, without being a priori an end in itself. Some criteria of decent work (ILO) are more widespread than others, however, the links with the desire to maintain an activity and the social and fulfillment dimensions tend to show that models of a job integrating the dimension of personal development remain prevalent. This study leads to a reflection on the value of the diploma, which had been meaningless in school and is now presented as a passport to renew professional life. It is true that the emerging adult finds work, but to aspire to more, he or she will have to undergo training, which is now essential for personal and professional development.
Keywords: decent work; meaning of work; young adults